Sustainable Branding Strategies: The Role of Ecopreneurship in Green Marketing and Consumer Loyalty - Arthur Simanjuntak; Zabenaso Queen; Rizki Galang Rahmadan; Henry Henry (Pandawan Sejahtera Indonesia, 2025)
In an era of increasing environmental awareness, consumers are not only concerned with product quality but also with the sustainability values embedded in a brand. Ecopreneurship, as an environmentally driven entrepreneurial approach, plays a crucial role in shaping sustainable branding strategies through the implementation of green marketing. This study aims to analyze the influence of ecopreneurship on sustainable branding and its impact on consumer loyalty. The main research problem addressed is how ecopreneurial practices and green marketing contribute to building consumer loyalty within environmentally conscious brands. A quantitative research method was employed, using a structured questionnaire distributed to 150 respondents who are consumers of eco-friendly products. Data were analyzed using SmartPLS 4 through the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The findings indicate that ecopreneurship significantly influences the implementation of green marketing strategies, which in turn positively affects brand image and consumer loyalty. Branding strategies that integrate sustainability values were found to foster emotional engagement, enhance consumer trust, and encourage repeat purchase behavior. The study concludes that ecopreneurship plays a vital role in developing a sustainable competitive advantage through environmentally focused branding. The practical implications suggest that businesses should holistically adopt sustainability principles in their branding communications to strengthen market positioning and foster longterm consumer loyalty.